Media CCT (Card of Critical Thinking) dalam Pembelajaran Matematika - Dyani Primaningsih (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2020)
One of the thinking skills can be developed through mathematics education is critical thinking. Teacher may take one of the steps to stimulate critical thinking skills by means of CCT (Cards of Critical Thinking) learning media. CCT is a learning media in the form of question cards; containing critical thinking questions like "is there something wrong, why it is wrong, and what should be done to correct the mistakes". The questions in this CCT met the criteria and indicators of critical thinking, namely FRISCO (Focus, Reason, Inference, Situation, Clarity, and Overview). The CCT is applied through the PBL (Problem Based Learning) approach. The main purpose of this literacy study is to describe teaching and learning steps through the application of CCT (Cards of Critical Thinking) to improve students' critical thinking skills.